Metaphysics Through Semantics: The Philosophical Recovery of the Medieval Mind Essays in Honor of Gyula Klima - Hochschild, Joshua P.; Nevitt, Turner C.; Wood, Adam; Borbély, Gábor (International Archives of the History of Ideas Archives internationales d'histoire des idées, 2023)
XXII, 410 p. 1 illus.